Extracellular signal-regulated kinases1/2 signaling pathways are not involved in endothelin regulation of mouse inner medullary collecting duct nitric oxide production - Hyndman, Kelly A (2012)
AIMS: To determine if endothelin-1 (ET-1) stimulates the phosphorylation of ERK1/2 in the mouse inner medullary collecting duct (IMCD), and if this in turn upregulates nitric oxide (NO) production. MAIN METHODS: Confluent mouse IMCD segment-3 cells (mIMCD-3) were stimulated with 50 nM ET-1 for 24 hrs with and without various doses of ET receptor antagonists, BQ123 (ETA antagonist,) or BQ788 (ETB antagonist) and phosphorylation of ERK1/2 determined by immunoblots. As well, NOS isoform expression and nitrite production were assessed. Finally, increasing doses of the MEK inhibitors, PD98,059 or U0126, were incubated with mIMCD-3 cells and the ET-1 dependent nitrite production determined. KEY FINDINGS: ET-1 via the ETB receptor significantly increased ERK1/2 phosphorylation, and was prevented by MEK inhibition. ET-1 also stimulates nitrite production by mIMCD-3 cells (basal: 54.5 ± 26 pmol/mg pr/h vs ET-1: 221 ± 28 pmol/mg pr/h; N= 4) via the ETB receptor (BQ788 + ET-1: 83.7 ± 27 pmol/ mg pr/h); however, ET-1 does not regulate NOS1 or NOS3 expression. MEK inhibition did not prevent the ET-1 stimulated nitrite production contrary to our initial hypothesis (vehicle + ET-1: 157 ± 13 pmol/mg pr/ hr vs PD98,059 + ET-1: 305.7 ± 24 pmol/mg pr/h, N= 4, P>0.05). SIGNIFICANCE: Although the mouse IMCD-3 cells only express the NOS1β splice variant, ET-1 did regulate mouse IMCD nitrite production. ET-1 stimulates ERK1/2 phosphorylation in the mouse IMCD, but ERK1/2 signaling is not involved in the ET-1 dependent increase in NO production by IMCD cells. Thus, we propose that ET-1 regulates protein-protein interactions that are necessary for NO production, that are independent of MAPK signaling cascades.